Research on measurement and management of energy consumption distribution of ship engines - Jipan Qiao; Jipan Qiao; Guanyu Guo; Ji An; Guohao Wu (Frontiers in Marine Science)
Intelligent ship energy efficiency online monitoring systems should possess the capability to monitor a ship’s primary energy-consuming equipment, navigation conditions, and other relevant parameters. In this study, the parameters obtained from engine test data were integrated into the system for verification purposes. The analysis focused on energy distribution and variations in the excess air coefficient under different loading conditions. The calculation results indicate that the proportions of turbocharger absorption power and shaft power increase with an increase in load, whereas the proportions of other losses decrease accordingly. Notably, the excess air coefficient exceeds 2 under each load condition and remains relatively constant after reaching 50% load. These findings suggest that the model meets the criteria for energy consumption monitoring. This methodology enables the pre-installation testing of system operation. Furthermore, this analytical approach facilitates engineers in assessing the engine’s operating state and provides insights for fault diagnosis based on changes in energy consumption distribution. It also empowers developers and managers to comprehend the direction of engine development.